Elevating nature: Moral elevation increases feelings of connectedness to nature. (October 2019) - Moreton, Sam G.; Arena, Andrew; Hornsey, Matthew J.; Crimston, Charlie R.; Tiliopoulos, Niko
Abstract: Moral elevation is a self-transcendent positive emotion arising from appraisals of moral excellence, which induces feelings of connectedness to other humans. However, no previous published research has investigated whether the effects of moral elevation extend to facilitate feelings of connection with the natural world. In two studies (Ns = 96 and 232), feelings of connectedness to nature were higher in people exposed to a moral elevation induction compared to a control condition. These effects were mediated by the extent to which participants reported experiencing self-transcendent positive emotions. Although Study 2 found significant indirect effects of elevation through self-transcendent positive emotions and connectedness to nature on measures of pro-environmental intentions, neither study found significant total effects of the elevation condition on these outcomes. Overall, the present studies provide preliminary evidence that inducing moral elevation increases feelings of connectedness to nature but mixed evidence regarding whether it increases immediate intentions to protect nature. Implications and future directions are discussed. Highlights: Moral elevation led to increased feelings of connectedness to nature. This effect was mediated by self-transcendent positive emotions. Moral elevation did not increase immediate pro-environmental intentions. The results support the role of social cognition in connectedness to nature.